Transforming Traditional Photovoltaic Panels into Thermal/ Photovoltaic Panels Incorporating Composite-Phase Change Materials - Ahmed, Mustafa K.; Khalifa, Abdul Jabbar N. (Al-Nahrain Journal for Engineering Sciences, 2024)
Solar panels are constantly evolving, with changes occurring in the materials used, panel shapes, and the method used to attach solar cells to the panels. Solar radiation consists of two components: photovoltaic energy, which is used to generate electricity via photovoltaic panels, and thermal energy, which, on the other hand, can reduce the efficiency of photovoltaic panels. Thermal photovoltaic panels are a recent breakthrough in the industry as they use light to generate energy and heat to reheat cryogenic liquid for a variety of purposes. One subtype that is gaining popularity is hybrid photovoltaic thermal panels, which are designed to enhance heat use by adding a heat storage medium, with phase change materials being a noteworthy example. ​ Despite their numerous benefits, these materials have limited heat conductivity, necessitating substantial research efforts to improve this attribute. However, most research focus solely on enhancing conductivity without applying the findings to PV panels in a comprehensive manner. This study fills this gap by reviewing the phase change materials accessible locally, picking Iraqi wax, researching additions, selecting micro- particles of aluminum oxide (Al2O3), investigating the mixing procedure, and calculating the ideal mixing ratio (6% additive to wax). The combination is then placed to a normal solar panel, resulting in a hybrid photovoltaic panel with a complicated phase transition material reinforced with aluminum oxide.